TUTUR BUMI: WASTRA TUU BATU DAN SAUDAN PADA KARYA ART FASHION - Ratna, Tjok Istri (PANGGUNG, 2024)
Bebali wastra is a sacred weaving product that contains aesthetic, socio-economic, and socio-cultural values with diverse meanings. The existence of bebali wastra is now starting to fade, so preservation efforts are needed. Therefore, innovation is carried out by adopting the visual aspects of tuu batu and saudan wastra into new wastra, then processed into art fashion products. The method used in the creation of art fashion products is Frangipani: The Secret Steps of Art Fashion. The result of the work is an innovation in tuu batu and saudan wastra through the making of tuu batu and saudan wastra replicas, which are used as the main medium to create six Tutur Bumi art fashion products. Creation was done through exploration with a combination of wastra saudan, tuu batuand various modern textiles painted to resemble rerajahan with the theme of the human life cycle related to Hindu ceremonies in Bali.